A pattern of empowerment in improving the professionalism of school supervisors - Nirwan, Akhmad (Jurnal Akuntabilitas Manajemen Pendidikan, 2017)
This study aims to obtain a pattern of empowerment to improve the professionalism of the school supervisors in Jakarta. This study employed the qualitative approach. The research subjects were school supervisors that consisted of key-informant, school supervisors’ colleagues, and coordinators of school supervisor. The data were collected through in-depth interviews, participant observation, and document analysis. The data were analyzed using qualitative data analysis techniques by Creswell Model. This study obtained an empowerment pattern of school supervisors to improve professionalism. There are five elements related to the empowerment pattern of school. First, the empowerment is the effort to develop themselves independently based on competencies and main duty. Second, empowerment is done by the implementation of CPD which is focused on the goals of empowerment and benefit in the increase of competencies, professionalism, responsibility, initiative, performance, and job satisfaction. Third, the constraints in the empowerment of school supervisor include the lack of facilities provided and low self- motivation of the school supervisors. Fourth, the solutions to overcome the constraints of the empowerment in improving the professionalism of the school supervisors include improving the commitment of all parties. Fifth, professionalism is defined as a full-time job, competence-based, having a code of ethics, having professional organization, doing their best, and making decision independently. Keywords: empowerment, professionalism, school supervisor POLA PEMBERDAYAAN DALAM MENINGKATKAN PROFESIONALISME PENGAWAS SEKOLAH Abstrak Penelitian ini bertujuan untuk menemukan pola pemberdayaan dalam meningkatkan profesionalisme pengawas sekolah di DKI Jakarta. Penelitian ini menggunakan pendekatan kualitatif dengan jenis fenomenalogis. Subjek penelitian ini adalah pengawas sekolah yang terdiri dari pemberi informasi utama, teman sejawat pengawas sekolah, dan koordinator pengawas sekolah. Data dikumpulkan melalui wawancara mendalam, pengamatan partisipasi, dan dokumentasi. Data dianalisis menggunakan model Creswell. Hasil penelitian ini menemukan pola pemberdayaan pengawas sekolah dalam meningkatkan profesionalisme. Ada lima unsur yang terkait dengan pola pemberdayaan pengawas sekolah. Pertama, pemberdayaan adalah usaha mengembangkan diri secara mandiri sesuai kompetensi dan bidang tugas. Kedua, pemberdayaan dilaksanakan melalui Pengembangan Keprofesian Berkelanjutan (PKB) yang fokus pada tujuan pemberdayaan dan bermanfaat untuk meningkatnya kompetensi, profesionalisme, tanggung jawab, prakarsa, kinerja, dan kepuasan kerja. Ketiga, hambatan pemberdayaan adalah belum adanya fasilitas yang memadai dan rendahnya motivasi pengawas sekolah. Keempat, solusi mengatasi hambatan pemberdayaan dalam meningkatkan profesionalisme pengawas sekolah adalah komitmen bersama semua pihak. Kelima, makna profesionalisme adalah kerja penuh waktu, sesuai kompetensi, punya kode etik, punya organisasi profesi, melakukan yang terbaik, dan membuat putusan mandiri. Kata kunci: pemberdayaan, profesionalisme, pengawas sekolah